Analisis Static Malware Menggunakan Algoritma Random Forest Machine Learning - Wijayanto, Febri; Putranto, Hasvid Dwi; Toriq, Farhan; Bhayangkara, Dimas Satrya (Universitas Respati Indonesia, 2023)
Malware is a malicious software program that aims to damage or steal data from a victim's system. Malware analysis is needed to determine the performance of the malware. Static analysis was used for feature extraction from a total of 10 PEfiles, 5 malware files and 5 benign files. The random forest machine learning algorithm obtained an accuracy of 99.99%.